SarS, a SarA Homolog Repressible by agr, Is an Activator of Protein A Synthesis in Staphylococcus aureus - Cheung, Ambrose L. (American Society for Microbiology, 2001)
The expression of protein A (spa) is repressed by global regulatory loci sarA and agr. Although SarA may directly bind to the spa promoter to downregulate spa expression, the mechanism by which agr represses spa expression is not clearly understood. In searching for SarA homologs in the partially released genome, we found a SarA homolog, encoding a 250-amino-acid protein designated SarS, upstream of the spa gene. The expression of sarS was almost undetectable in parental strain RN6390 but was highly expressed in agr and sarA mutants, strains normally expressing high level of protein A. Interestingly, protein A expression was decreased in a sarS mutant as detected in an immunoblot but returned to near-parental levels in a complemented sarS mutant. Transcriptional fusion studies with a 158- and a 491-bp spa promoter fragment linked to the xylE reporter gene disclosed that the transcription of the spa promoter was also downregulated in the sarS mutant compared with the parental strain. Interestingly, the enhancement in spa expression in an agr mutant returned to a near-parental level in the agr sarS double mutant but not in the sarA sarS double mutant. Correlating with this divergent finding is the observation that enhanced sarS expression in an agr mutant was repressed by the sarA locus supplied in trans but not in a sarA mutant expressing RNAIII from a plasmid. Gel shift studies also revealed the specific binding of SarS to the 158-bp spa promoter. Taken together, these data indicated that the agr locus probably mediates spa repression by suppressing the transcription of sarS, an activator of spa expression. However, the pathway by which the sarA locus downregulates spa expression is sarS independent.